FENOMENA KEBUTUHAN PANGAN ASAL DAGING DAPAT DIPENUHI MELALUI PENINGKATAN USAHA SAPI POTONG DI PETANI - Supardi Rusdiana (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2019)
The phenomenon of food needs from beef always increases. But it can be met through imports, to meet the needs of the community. The Government Program focused on increasing beef cattle production needs to be supported and worked together, so that the program can run well. Based on these problems, the Government has so far fulfilled the food needs of beef by import. The income of farmers from beef cattle business is not optimal and the business is still a side business that has not led to commercial businesses or basic livestock businesses. The purpose of this review is to try to review the phenomenon of food needs from beef, which can be fulfilled through increasing beef cattle business in farmers. The government's commitment to pursue beef cattle population is a target for food sufficiency from beef for 2026. Indonesia will no longer import beef and live cattle. Bali cattle and PO cattle can be maximized in their potential to produce calves and produce meat. The results of Bali Betina cattle farmer farmers get a profit of IDR 5,464,000- /year B/C 1.3 and the effort to collect PO farmer male beef cattle will get a profit of Rp.4,575,000.-/B/C period 1.2. In addition to beef cattle business can increase farmers' income and indirectly can meet food needs from dagig cattle.